2022
DOI: 10.3390/su142416468
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Climate Change, Carbon Dioxide Emissions (CO2) and Renewable Energy Consumption on Agricultural Economic Growth in South Africa: ARDL Approach

Abstract: One of the most affected economies by climate change is the agricultural sector. Climate change measured by temperature and precipitation has an impact on agricultural output, which in turn affects the economy of the sector. It is anticipated that using renewable energy will lower carbon emissions that are directly related to climate change. The main objective of this study was to evaluate the impact of carbon dioxide emissions (CO2), renewable energy usage, and climate change on South Africa’s agricultural se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…However, this requires funding, which is inaccessible to small-scale farmers. Although small-scale farmers have the potential to meaningfully participate in producing renewable energy through bioenergy, the lack of green energy investment in the small-scale agricultural sector hampers this opportunity (Tagwi, 2022Tagwi and Chipfupa, 2022). Most small-scale farmers in Limpopo province in cooperatives reported an inability to cope with electricity costs due to 3-phase transformers installed in the farming plots by ESKOM which attracts higher rates (Maiwashe, 2017).…”
Section: Determinants Of Climate Change Adaptation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this requires funding, which is inaccessible to small-scale farmers. Although small-scale farmers have the potential to meaningfully participate in producing renewable energy through bioenergy, the lack of green energy investment in the small-scale agricultural sector hampers this opportunity (Tagwi, 2022Tagwi and Chipfupa, 2022). Most small-scale farmers in Limpopo province in cooperatives reported an inability to cope with electricity costs due to 3-phase transformers installed in the farming plots by ESKOM which attracts higher rates (Maiwashe, 2017).…”
Section: Determinants Of Climate Change Adaptation Strategiesmentioning
confidence: 99%
“…Climate change is widely caused by fossil fuel energy use currently dominating the world. The future food demand will put a strain on natural resources, especially energy sources (Tagwi, 2022), further making food security a challenge. Considering that most rural households depend on agriculture for livelihood across Africa, this will put immense pressure on the agricultural sector.…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated that decreasing agricultural productivity as an outcome of global warming brought on by carbon emissions had negatively impacted food availability. Tagwi (2022) assessed the effects of environmental degradation, green power use, and greenhouse gas pollution on South Africa's farming industry from 1972 to 2021. An econometric method called the Auto Regressive-Distributed Lag (ARDL) Bounds test was used to analyze the association.…”
Section: Chidiebere-mark Et Al (2022) Examined the Relationship Betweenmentioning
confidence: 99%
“…The effects of the climate shocks are being felt harder in developing countries like Zimbabwe (Aluwani, 2022). This is largely attributed to the economic fragility, as well as the lack of technical and institutional capacity.…”
Section: Introductionmentioning
confidence: 99%